Review on security risks of key components in industrial control system - Shijie TANG; Fang YUAN; Jun LI; Yong DING; Huiyong WANG (网络与信息安全学报)
With the rapid development of modern information technology and communication technology, industrial control system has become an important part of national key infrastructure, whose security is related to national strategic security and social stability.The close connection between modern industrial control system and Internet promotes the rapid progress of industrial control technology, meanwhile it brings serious security risks.Since the“Stuxnet” virus incident, attacks on industrial control systems have occurred frequently, which causes huge economic losses to global production enterprises.Besides, it also poses significant impact on the social stability and security to many countries and regions, which has aroused people’s great concern about the security of industrial control systems.Due to the wide variety of automation equipment and proprietary protocols, complex data flow and rapid development in modern industrial control system, it is very difficult to summarize the safety of key components of industrial control.There are few literatures related to this area, and most of them are old and incomplete.To solve the above problems, the mainstream architecture and related components of the current industrial control system were introduced.Then the security vulnerabilities and potential threats in the key industrial control components were analyzed.The attack methods of SCADA control center, programmable logic controller and field equipment were summarized.Furthermore, the preconditions, objects, steps and hazards of the attack in the literature in recent years were also analyzed.The attacks against industrial control network were classified from the perspective of integrity and confidentiality.Finally, the possible development trend of industrial control system attack was given.